Mobile-izing health workers in rural India - Ramachandran, Divya; Canny, John; Das, Prabhu Dutta; Cutrell, Ed (CHI '10: Proceedings of the 28th international conference on Human factors in computing systems, 2010)
Researchers have long been interested in the potential of ICTs to enable positive change in developing regions communities. In these environments, ICT interventions often fail because political, social and cultural forces work against the changes ICTs entail. We argue that familiar uses of ICTs for information services in these contexts are less potent than their use for persuasion and motivation in order to facilitate change. We focus on India’s rural maternal health system where health workers are employed in villages to persuade pregnant women to utilize health services. Health workers face challenges due to resistance to change in the village, and because of their limited education, training and status. These factors appear to reduce the motivation of health workers and impair their performance. For two months, we deployed short videos on mobile phones designed to persuade village women and motivate health workers. We also asked health workers to record their own videos. While our results are preliminary, they show evidence that the creation and use of videos did help (1) engage village women in dialogue, (2) show positive effects toward health worker motivation and learning, and (3) motivate key community influencers to participate in promoting the health workers.
Best of CHI Award